Pengaplikasian Baterai Lithium Ion pada DYE Sensitized Solar Cell (DSSC) dengan Sistem Building Integrated Photovoltaic (BIPV) Rumah Tinggal - Daya Wulandari; Riztamala Diana; Leila Utarina; Mitha Pratiwi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Solar energy can be converted into electricity using photovoltaic systems as a strategic measure to achieve the renewable energy mix targets outlined in the National Energy Policy. Photovoltaic Rooftop (PV Rooftop) systems integrated with Building Integrated Photovoltaics (BIPV) present a viable alternative. PV Rooftop technology is currently trending, as evidenced by its increasing adoption in both industrial and residential sectors, supported by the global decline in solar panel prices. However, from an architectural perspective, silicon-based PV panels can reduce the aesthetic appeal of buildings. An emerging solution promoted by architects worldwide is the implementation of semi-transparent, dye-sensitized solar cells (DSSC), which are sensitive to colorants. In addition to their functional properties, DSSCs offer high aesthetic value due to the pigments used. Urban areas hold significant potential for the development of off-grid DSSC photovoltaic systems installed on rooftops and building facades. This study focuses on the analysis of off-grid DSSC PV systems for a type 42 residential house in Palembang City. The research employs a quantitative approach, using literature review and field measurements, followed by technical calculations. The article details the components required for designing an off-grid DSSC photovoltaic system capable of supplying all household electrical loads.